Elite Bargains and Political Deals Project: Mozambique Case Study - Vines, Alex (UK Government Stabilisation Unit, 2018)
This case study is one of a series commissioned to support the Stabilisation Unit’s (SU) development of an evidence base relating to elite bargains and political deals. The project explores how national and international interventions have and have not been effective in fostering and sustaining political deals and elite bargains; and whether or not these political deals and elite bargains have helped reduce violence, increased local, regional and national stability and contributed to the strengthening of the relevant political settlement. Drawing on the case studies, the SU has developed a series of summary papers that bring together the project’s key findings and will underpin the revision of the existing ‘UK Approach to Stabilisation’ (2014) paper. The project also contributes to the SU’s growing engagement and expertise in this area and provides a comprehensive analytical resource for those inside and outside government
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - north / norte; GP - Nampula; L - english / inglês; conflict - civil war / conflito - guerra civil; conflict / conflito; decentralization / descentralização; electoral geography / geografia eleitoral

Os Municípios dos “Outros”. Alternância do poder local em Moçambique? O caso de Angoche - Rosário, Domingos Manuel do (Cadernos de Estudos Africanos, 2015)
As eleições municipais de 2003 marcaram o início do exercício do poder local pela Renamo no município de Angoche. Quais são os factores explicativos desta situação eleitoral local? A partir de uma perspectiva sócio-histórica, este artigo procura compreender como é que a evolução política e administrativa destes territórios influenciou a lógica do poder local. São as relações estabelecidas entre as populações e o Estado e a forma como a municipalização foi desenhada e implementada desde 1994 pela Frelimo que não proporcionam condições favoráveis à criação de um pluralismo político, na medida em que o partido dominante consegue, através do controlo que exerce sobre o Estado central, instrumentalizar os recursos e fortificar suas bases políticas e eleitorais.
Number: 30
Keywords: *tagged; G - Mozambique / Moçambique; G - north / norte; GD - Angoche; L - portuguese / português; Northern PEA; electoral geography / geografia eleitoral